ANiSHA : ACCIDENTAL DETECTIVE : FRIGHT NIGHT! - Patel, Serena; McCann, Emma (London : Usborne Publishing Ltd., 2022)
This book of first words is all about YOU. There are lots of things to name and spot-and plenty of little holes to look through.
Keywords: English fiction; Detective and mystery stories, English